Two hydrazone copper(ii) complexes: synthesis, crystal structure, cytotoxicity, and action mechanism. Issue 42 (12th April 2016) - Hu, Kun; Zhou, Guimei; Zhang, Zhong; Li, Feiyan; Li, Jingui; Liang, Fupei
Abstract : Two hydrazone copper(ii ) complexes1 and2 exhibited significantly cytotoxicity. MGC80-3 cells are more sensitive to complexes versus normal liver cells. And the mechanism of cell cytotoxicity against the MGC80-3 cancer cell was studied. Abstract : Two copper(ii ) complexes with 8-quinolinecarbaldehyde o -vanilloylhydrazone (H-L1) and 8-quinolinecarbaldehyde salicylhydrazone (H-L2), [Cu(L1)NO3 ] (1 ) and [Cu(L2)NO3 ] (2 ), were synthesized and structurally characterized, respectively. Complexes1 and2 exhibited enhanced cytotoxicity against BEL-7402, Hep-G2, NCI-H460, MGC80-3, HeLa tumor cells compared with free ligands and copper(ii ) salt and slightly lower than that shown by cisplatin. And MGC80-3 cells are more sensitive to these two complexes relative to the normal liver cells. Cytotoxicity and action mechanism studies suggest1 and2 could cause MGC80-3 cell cycle arrest at G1 phase, which is induced by limiting the supply of cyclins D1 and E1 and inhibiting the activity of G1-phase-promoting cyclin–Cdk complexes. And complexes1 and2 led to cell apoptosis via the activation of Bcl-2 protein. Moreover, mitochondrial dysfunction was induced by both of complexes.